Early marriage and fertility outcomes in South-East Nigeria. - Ozumba, Chineme O. I. (My University, 2013)
Background: Despite the adverse demographic and health impact of early marriage, it still occurs in many developing nations including Nigeria. One of the outcomes of early marriage is increase in population size due to the number of years of exposure to the risk of pregnancy of women who marry early. Most of the research on early marriage has been carried out in the Northern and Western zones of the country. The objective of this study was to identify the relationship between early marriage and the outcomes of Number of Children Ever Born (NCEB) and Total Fertility Rate (TFR) in the South East Zone (SEZ) of the country. Methods: Univariate, bivariate and multivariate analysis were carried out on data obtained from 2008 Nigeria Demographic and Health Survey (NDHS) to determine the relationship between NCEB and age at first marriage as well as other independent variables such as woman’s level of education, wealth status, place of abode, husband’s educational level and marital status for ever married women aged 45-49 years. TFR was estimated for all ever married women in the South East Zone as well as those who married at <18 years and those who married at >=18 years of age. A sample size of 2175 comprising all ever married women in the SEZ was used for the study. Results: The findings indicate that there is a significant relationship between NCEB and Age at first marriage as well as woman’s level of education only. The TFR for women who married at <18 years and 18+ was 7.8 and 7.7 respectively. Conclusions: The study has shown that early marriage contributes in some measure to the number of children born in South Eastern Nigeria. However the level of significance is low. The seeming contradiction suggests that there are other influencing factors such as prevailing customs and traditions and shared experiences of the Igbos (the dominant tribe in the study area). Areas of further research are highlighted and recommendations for policy and program implementation are made.
Keywords: Marriage age--Nigeria; Fertility, Human--Nigeria--Statistics.; Family size--Nigeria